2010
DOI: 10.1504/ijttc.2010.029426
|View full text |Cite
|
Sign up to set email alerts
|

Reward, risk and response in Australian cooperative research centres

Abstract: Cooperative research centres are a well-established organizational embodiment of the 'triple helix' . As complex inter-organizational structures they are subject to diverse management strategies. The imperatives that drive their strategic plans and their impact on partner organizations and the careers of the scientists who work within them are not well understood. We examine 370 participants' experience in Australian Cooperative Research Centres and consider their effect on personnel and organizations in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…However, few studies have cited administrative support acquisition as a reason to collaborate. In the case of international research centers, study participants have found management structures in these centers to be administratively burdensome ( Turpin and Garrett-Jones, 2010 ). Collaboration between individuals and institutions creates more administrative and management needs, which may offset the benefits of collaborating by the need to access shared administration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, few studies have cited administrative support acquisition as a reason to collaborate. In the case of international research centers, study participants have found management structures in these centers to be administratively burdensome ( Turpin and Garrett-Jones, 2010 ). Collaboration between individuals and institutions creates more administrative and management needs, which may offset the benefits of collaborating by the need to access shared administration.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers will look for collaborators in an effort to pool and leverage funds and share the cost of projects ( Birnholtz, 2006 ; Fox and Faver, 1984 ; Georghiou, 1998 ; Katz and Martin, 1997 ; Kraut et al, 1987 ; Wagner and Leydesdorff, 2005 ). While some rank monetary gains as a primary motivator for collaboration ( Langford et al, 2006 ; Lee, 2000 ), others place less importance on these financial benefits when compared to other intangibles ( Turpin and Garrett-Jones, 2010 ). The need to access funds appears to be motivated by a desire to advance one's own research agenda rather than the potential for personal financial gains, even in industry-academia collaborations ( D’Este and Perkmann, 2011 ; Lee, 2000 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demands of an entrepreneurial approach require focusing on execution, the short term transformation into sellable products, and the obtainment of profit. Such a transformation is influenced by economic and other intangible stimuli (Turpin and Garrett-Jones 2010) through the incentives and rewards system operating in job appointments and scientific careers.…”
Section: The Contested Terrain Of University-industry Relationshipsmentioning
confidence: 99%
“…These internal conflicts can impede one's ability to adequately share information, trust a team or network, and even hamper the advancement of a science program especially if knowledge is withheld as a result of such insecurities . Loss aversion (Fox & Faver, 1984;Georghiou, 1988;Sonnenwald, 2007), lack of recognition and reward (Dasgupta & David, 1994;Turpin & Garrett-Jones, 2010), concerns about achieving promotion and tenure (Carayol & Thi, 2005;Coleman, 1986;Harris, Lyon, & Clarke, 2009;Horlick-Jones & Sime, 2004;Maglaughlin & Sonnenwald, 2005;Rhoten & Parker, 2004;Zucker, 2012), and authorship embattlements (Barrett, Funk, & Macrina, 2005;Lewis, Ross, & Holden, 2012;Stokols et al, 2008) are just a few of the issues that can ensue from within a scientific team that struggles with diverse attitudes about knowledge sharing.…”
Section: Attitudes About Ownership Of Knowledgementioning
confidence: 99%